ANALISIS PENENTUAN TARIF RAWAT INAP DENGAN METODE ACTIVITY BASED COSTING PADA RSUD HAPSARI MEDIKA KOTA LUBUKLINGGAU - Miranti, Bunga; Triharyati, Eri (Universitas muhammadiyah palembang, 2015)
The background of this research is Hapsari Medika Hospital who calculate hospitalization room rates on the basis of unit cost, although the calculation of rates of hospitalization has been regulated by the government based on the unit cost, but the hospital will be able to apply a calculation based onActivity Based Costing System for consideration. The research objective is to increase knowledge about the determination of Tariff Inpatient by using Activity Based Costing as well as being one of the inputs which provideinformation on the Activity Based Costing, especially in setting of a hospital. Data collection techniques are documentation, and data analysis used is quantitative analysis and Kualitatif.Hasil calculations showed that the hospitalization rates by using activity based costing, when compared with the rates used by the hospital, the activity based costing deliver greater results for VIP class, Class II and Class III, as well as providing smaller yieldfor Class I. This is because loading the overhead on each product. On activity based costing, overhead on each product charged to the many cost driver. So in activity based costing, has been able to allocate costs accurately kam kesetiap activity based on consumption respectively.